Editorial: good news to patients with thalassaemia—HCV clearance made easy with direct acting antivirals. Authors' reply. Issue 6 (14th August 2017) - Mangia, A.; Piazzolla, V.; Santoro, R.
Abstract : Linked Content This article is linked to D'Ambrosio, Lampertico and Mangia et al papers. To view these articles visithttps://doi.org/10.1111/apt.14221 andhttps://doi.org/10.1111/apt.14197 .